Fitness education for children a team approach - Virgilio, Stephen J (Human Kinetics, 2012)
Emphasizes the importance of collaboration to combat obesity and promote active lifestyles. This book shows how you can engage with the efforts of physical educators, classroom teachers, school volunteers, parents and others in the community by offering information on incorporating the team approach to help schools meet wellness policy objectives.